Effectiveness of Spinach Leaf Extract (Amaranthus spinosus L.) as an Anti-inflammatory against Paw Edema of White Rats (Rattus norvegicus) - Aisyah, Sitti; Fauziah, Sitti (Al-Kimia, 2024)
Spinny leaves (Amaranthus spinosus L.) are widely used in traditional medicine in the community, apart from their function as a food ingredient. Spinach leaves contain active compounds that can treat inflammation. This study investigates the effect of thorn spinach leaf extract on carrageenan-induced oedema of the legs of female white rats (Rattus norvegicus). An experimental method with a randomized block design (RAK) was employed, which consisted of five treatments and three repetitions. The study results showed that spinach leaf extract (Amaranthus spinosus L.) significantly reduced carrageenan-induced inflammation in the feet of female white rats. The anti-inflammatory effect of spinach leaf extract is practical at a dose of 1250 Mg/kg BW.